2022
DOI: 10.1108/cg-04-2021-0151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of founder CEO duality and board size on foreign IPOs’ survival in US markets

Abstract: Purpose This study aims to investigate how three critical governance decisions by foreign firms impacted their survivability post-initial public offerings (IPO): the choice of CEO (founder vs non-founder); the power the founder CEO wields relative to the board in terms of CEO duality; and board size. Design/methodology/approach This study uses data from 86 foreign firms that completed IPOs in the US market between 2000 and 2008 and adopts a Cox proportional hazards model to examine how the founder, founder C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 172 publications
2
10
0
Order By: Relevance
“…So, based on findings, effective board size favors the shareholder interest by maintaining minimum capitalization and shifting the risk from shareholder to debt holder in the Pakistani context. While in the case of CEO duality, findings also show a significant negative relationship, which is also consistent with the study of Lee and Ko ( 2022 ). Board independent non-executive directors and dividend payout ratio are in support of the fourth hypothesis, which states that there is a relationship between independent non-executive directors and dividend payout ratio among the Malaysian sample companies, which these results also support (Subramaniam et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…So, based on findings, effective board size favors the shareholder interest by maintaining minimum capitalization and shifting the risk from shareholder to debt holder in the Pakistani context. While in the case of CEO duality, findings also show a significant negative relationship, which is also consistent with the study of Lee and Ko ( 2022 ). Board independent non-executive directors and dividend payout ratio are in support of the fourth hypothesis, which states that there is a relationship between independent non-executive directors and dividend payout ratio among the Malaysian sample companies, which these results also support (Subramaniam et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…As such, they did not find strong or consistent evidence of superior long-run investment performance on the part of founder-CEO-led IPO firms relative to similar non-founder-CEO-led IPO firms. An analogous conclusion was also reached by Lee and Ko (2022) who in their research could not support a presumption of a positive correlation between the presence of founder-CEOs and the foreign firms' longer term survival post-IPO. Willard et al (1992) found no significant differences in performance between foundermanaged and professionally managed firms in the study of 155 mostly high-tech manufacturing firms from the list of the 100 fastest-growing publicly held firms in U.S. On average, founder-managed firms were somewhat (but not significantly) smaller and were growing at a slightly (but not significantly) lower rate.…”
Section: Performancementioning
confidence: 74%
“…Usually, researchers in the field of performance differences of founder-CEO-led and professional-CEO-led companies base their research on publicly available data of IPO companies that are listed on the stock exchanges (e.g., Lee & Ko, 2022;Lee et al, 2020;Mousa et al, 2014;Gao & Jain, 2011) with the main measure being stock market performance. This approach was not valid in the case of Lithuanian companies since the Nasdaq Vilnius stock exchange had only 25 companies listed combined on the Main and Secondary lists as of August 1, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Beddoe's different sources of power—formal (both CEO and chair and large ownership stake) and informal (founder stature, tenure, firm‐ and industry‐specific knowledge, and external networks)— created a power bundle which, in combination with his discretion, explains why duality at WestJet worked well for eight years. This configurational approach (Lewellyn & Fainshmidt, 2017) also facilitated our inclusion of other contexts, like organizational life cycle stage (Elsayed, 2007) and role of the founder/CEO (Lee & Ko, 2022), in the analysis of WestJet.…”
Section: Discussionmentioning
confidence: 99%
“…In view of these difficulties, some researchers have examined the effectiveness of board structure under a host of internal and/or external contexts, that is, environmental and temporal conditions (Brockman et al., 2004), degree of informal CEO power, firm performance, and the need for quick, decisive decision‐making (Finkelstein & D’Aveni, 1994), CEOs' motivational power (Martin & Butler, 2017), and founding CEO status (Lee & Ko, 2022). Other researchers have examined how internal and/or external contingencies dictate the relation between board structure and firm performance, that is, the nature of the industry (Boyd, 1995), family ownership stake (Braun & Sharma, 2007), the influence of top executives and block‐holding outside directors (Tang, 2017), and the “loan insider CEO,” that is, the CEO being the only board insider (Zorn et al., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%